Carbapenem-nonsusceptible strains of Klebsiella pneumoniae producing SHV-5 and/or DHA-1 beta-lactamases in a Czech hospital - Chudácková, Eva; Bergerová, Tamara; Fajfrlík, Karel; Cervená, Dana; Urbásková, Pavla; Empel, Joanna; Gniadkowski, Marek; Hrabák, Jaroslav (FEMS microbiology letters, 2010)
Resistance to carbapenems in enterobacteria is mediated by the production of several types of carbapenemases or by the decreased permeability of the outer membrane, combined with the expression of extended-spectrum beta-lactamases (ESBLs) or AmpC-like cephalosporinases. The objective of this study was to characterize carbapenem-nonsusceptible (C-NS) isolates of Klebsiella pneumoniae in the University Hospital in Plzen (Czech Republic) and compare them with carbapenem-susceptible (C-S) K. pneumoniae isolates from the same patients. Six C-NS K pneumoniae isolates from different patients were collected between January 2007 and June 2008, and from three of these patients, C-S isolates were available for the study as well. The isolates were typed by pulsed-field gel electrophoresis and multilocus sequence typing. beta-Lactamases were analyzed by isoelectric focusing, bioassay, and PCR and sequencing of bla genes. Major porin channels, OmpK35 and OmpK36, were studied by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot; porin genes were amplified and sequenced, and their expression was assessed by reverse transcriptase-PCR. The C-NS isolates belonged to three pulsotypes and to the clone ST11, produced the SHV-5 ESBL and/or DHA-1 AmpC-type cephalosporinase, did not express OmpK36, and had a reduced expression of OmpK35. The C-S isolates differed from their C-NS counterparts only by porin expression profiles.
Keywords: Hospitals; Klebsiella Infections; infekce bakteriemi rodu Klebsiella; Bacterial Proteins; techniky typizace bakterií; Česká republika; Drug Resistance, Bacterial; antibakteriální látky; beta-Lactamases; Microbial Sensitivity Tests; karbapenemy; Klebsiella pneumoniae; beta-laktamasy; Czech Republic; lidé; Anti-Bacterial Agents; Carbapenems; Humans; bakteriální léková rezistence; mikrobiální testy citlivosti; bakteriální proteiny; Bacterial Typing Techniques; nemocnice